Employing artificial intelligence to generate drawings and designs of sculptural forms (Al-Academy, 2024)
The idea of the research is to employ Artificial Intelligence (AI) tools used in generating preliminary drawings and designs in fine art and sculpture in particular, and ways to benefit from them in helping artists and art students and presenting different ideas and styles, as well as saving effort and time and with high accuracy keeping pace with contemporary developments, and after reviewing the Sources and the Internet: About 50 regular and generative artificial intelligence tools were identified, which differ in terms of characteristics, methods of use, ability to generate various outputs, and the work and application of them. Three of these tools (Pixler AI - Midjourney – Fooocus AI) were chosen to be the applications that generate models for our research sample, which resulted in the Midjourny tool being distinguished due to its distinction in providing sculptural designs that carry high aesthetic and standard values, so it is considered the best. In terms of its use in generating and creating innovative and diverse drawings and sculptural designs, it is followed by Pixler and then Fooocus